2011
DOI: 10.1111/j.1708-8208.2011.00377.x
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Bone‐Level Alterations at Implants Installed in Block versus Particulate Onlay Bone Grafts Mixed with Platelet‐Rich Plasma in Atrophic Maxilla. A Prospective 5‐Year Follow‐Up Study of 15 Patients

Abstract: The present follow-up study showed that there is no significant difference in the extension of resorption between block- and particulate autogenous bone grafts over a 5-year period. Most of the resorption occurred during the first year in function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
0
34
1
Order By: Relevance
“…,b; Dasmah et al. ). Twenty‐four prospective studies used conventional radiographs to determine the MBL (von Arx et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…,b; Dasmah et al. ). Twenty‐four prospective studies used conventional radiographs to determine the MBL (von Arx et al.…”
Section: Resultsmentioning
confidence: 99%
“…; Dasmah et al. ) and the remaining studies evaluated peri‐implant tissue stability after implant placement in previously augmented bone (von Arx et al. ; Hellem et al.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of bias for the included non‐randomized studies according to the ROBINS‐I tool is presented in Figure b and Supporting Information Appendix b. None of the studies were in a low risk of bias: one had signs of moderate bias (Beitlitum, Artzi, & Nemcovsky, ), five of serious bias (Barbu et al., ; Cordaro et al., ; Maiorana, Beretta, Salina, & Santoro, ; Shalash et al., ; Urban et al., ) and three of critical bias (Chiapasco, Abati, Romeo, & Vogel, ; Dasmah, Thor, Ekestubbe, Sennerby, & Rasmusson, ; Monje et al., ). The domain “bias due to confounding” was a source for critical risk of bias for three studies with overall critical risk of bias (Chiapasco et al., ; de Freitas et al., ; Monje et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…[13][14][15] In addition, the analysis showed that implants placed in bone augmented with allograft onlays were even longer than those placed in bone augmented with autograft onlays. This is probably because of the vertical bone resorption that occurs in autograft onlays during the first year after onlay placement, 68 although further clinical studies are needed to investigate the difference of onlay graft resorption between autograft and allograft onlays.…”
Section: Implant Lengthmentioning
confidence: 99%